Artificial Intelligence Pengetahuan Agama Dan Lingkungan Siswa Sadar Mengelola Sampah - Sanny; Yuliana, Liza; Fauzi, Rezki (Journal of Computer Science and Informatics Engineering, 2023)
Religion plays an important role in human life. Religion has a very dominant role in the formation of human personality because religion is the main source of foundation in the dimension of human life in shaping human personality, through disclosing spiritual values, creed values, worship practices, so as to give birth to individuals who are obedient and diligent in carrying out religious values. Obedience and adherence to religious values ​​not only shape individual personality, but are manifested from these personality values ​​can organize their lifestyle so that they can live life in a calm, orderly and neat manner. In this study, it is seen how the role of students' knowledge of religion and the environment has on the level of awareness of these students in managing waste, especially in the school environment. Using a total sample of 100 students, questionnaires are administered and the results obtained are processed with artificial intelligence using the rough set method. The results obtained were 8 new rules which were set as a reference in the future to change the behavior of students who are aware of better waste management.